Factors Associated With The Occurrence Of Sectio Caesarea Delivery In The Hospital Dr. Agoesdjam Ketapang, 2022 - Vika VAprianti; Sukarni Setia Ningsih (International Journal of Health and Pharmaceutical (IJHP), 2024)
Usually, doctors recommend vaginal or cesarean delivery if the pregnancy is at risk. causes of a cesarean section carried out for indications of the mother or fetus, including: history of cesarean section if the distance between pregnancy and birth is less than 2 years, the birth process is not progressing, the fetal position is flat, the size of the baby's head or body is too large for normal delivery, the mother has other problems. health problems that put you at risk, such as high blood pressure, diabetes or heart disease, mothers with health conditions that put you at risk, such as genital herpes or HIV, quoted from the NHS website, mothers of small children because they often have a small pelvis, have had surgery past cesarean delivery, had problems with the placenta, such as placenta previa or placenta previa, baby's umbilical cord problems, babies with birth defects, twin pregnancies, triplets or more, babies in the womb with health problems, such as hydrocephalus or uterine fibroids, mother with uterine problems or fibroids blocking the cervix (cervix). This research is a descriptive study and the data used in this study is secondary data from the medical records of patients who underwent caesarean sections at Dr Agoesdjam Ketapang Hospital in 2022.Based on the results of multivariable analysis, it is known that the factor most related to the number of caesarean sections is the number of births with a p-value of 0.000 (p-value <0.05), with a standard deviation of 14.05. In other words, it can be concluded that the more negative the birth history, the higher the caesarean section rate.